Níveis e fontes de selênio em dietas para pós-larvas de tilápia do Nilo. - Batista, João Marcos Monteiro (2019)
The objective was to evaluate different levels and sources of selenium in diets for Nile tilapia post-larvae, on productive performance, muscle fiber morphology. 1260 post- larvae with an initial average weight of 0.010 g were used, distributed in a completely randomized design, in a factorial scheme with four levels of selenium supplementation (0.6; 0.9; 1.2 and 1.5 mg / kg of Se ) and two sources (sodium selenite and selenium yeast), plus one control, total nine treatments and four repetitions each, and 35 post-larvae distributed in each fiberglass aquarium, total of 36 containers. The physical-chemical parameters of water quality were within the recommended for the production of tilapia. Productive performance was not affected (p> 0.05) regardless of the level and source of selenium in the diets. However, the effect of the yeast selenium source was observed, with higher feed intake (p <, 0001). As well as for the hepatosomatic index, it was higher (p <0.05) for post-larvae that received selenium in yeast diets. In the factor diets containing selenium sources, compared to the control diet, it was found (p <0.05) in the variables final height, final width, specific development rate and protein efficiency rate. What was not evidenced (p> 0.05) for muscle fiber morphometry with selenium supplementation. It is concluded that in the post-larvae phase of Nile tilapia, the level of 0.6 mg of selenium / Kg of feed, regardless of the source to be used, is sufficient for this development phase to present an excellent zootechnical performance.